2015
DOI: 10.1007/s11540-015-9290-8
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Uptake, Use Efficiency, and Response of Potato Cultivars to Phosphorus Levels

Abstract: Utilization of potato (Solanum tuberosum L.) cultivars with greater phosphorus (P) efficiency and response to application of this nutrient is essential to maximize yield, mainly in tropical soils that usually have low P availability. An experiment was conducted under greenhouse conditions in order to evaluate the P uptake rate and the P efficiency for dry matter (DM) production and tuber yield of five potato cultivars (Agata, Asterix, Atlantic, Markies, and Mondial) under low (15 mg dm −3 P) and high (150 mg d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
4
35
0
2
Order By: Relevance
“…At the highest dose of phosphorus, Asterix varieties were responsive to P application, with yields similar to the Ágata variety. Phosphorus responsive Atlantic varieties may not yield to high yields if tuber dry matter partitioning is low (Soratto et al, 2015). These authors attribute this effect to the greater efficiency of some varieties at absorbing P, and to the fact that certain varieties are more productive than others.…”
Section: Resultsmentioning
confidence: 99%
“…At the highest dose of phosphorus, Asterix varieties were responsive to P application, with yields similar to the Ágata variety. Phosphorus responsive Atlantic varieties may not yield to high yields if tuber dry matter partitioning is low (Soratto et al, 2015). These authors attribute this effect to the greater efficiency of some varieties at absorbing P, and to the fact that certain varieties are more productive than others.…”
Section: Resultsmentioning
confidence: 99%
“…The largest increases in potato tuber yield have come from P applications, especially in P-deficient soils (Fontes et al, 1997;Alvarez-Sánchez et al, 1999;Rosen and Bierman, 2008;Soratto et al, 2015;Fernandes and Soratto, 2016), although K, N, and Ca are taken up in greater amounts by potato plants (Fernandes et al, 2011). Since costs are high in establishing the potato crop, many farmers prefer to ensure high yields through possible over application of fertilizers than to adhere to the recommended levels for fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…A balanced P supply can increase the dry matter yield (DM) and P uptake by potato plants (Alvarez-Sánchez et al, 1999;Jenkins and Mahmood, 2003;Fernandes and Soratto, 2012b;Soratto et al, 2015;Soratto and Fernandes, 2016) and, additionally, can affect the uptake and concentration of other nutrients in different parts of plants that are grown in the nutrient solution (Barben et al, 2010a,b;Fernandes and Soratto, 2012b) or soil (Jenkins and Mahmood, 2003;Fernandes et al, 2015;Munda et al, 2015;Soratto and Fernandes et al, 2016). In P-deficient soil, phosphate fertilization increased the uptake and removal of most nutrients as well as growth and tuber yield in the Agata and Mondial potato cultivars (Soratto and Fernandes, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in potato have shown important genotypic differences in P uptake efficiency (Soratto et al, 2015;Sandaña, 2016). This implies that the relationship between relative yield and soil Olsen-P and, as a result the critical Olsen-P value, can be affected by the genotype.…”
Section: Relative Yieldmentioning
confidence: 95%